(untitled) (Bioagro, 2024)
Research in the Eastern Mediterranean Transition Region of Türkiye has demonstrated that plant density impact yield of peanut (Arachis hypogaea L.) cultivars differentially. It is suspected that interactions of plant density and cultivar could also impact oil quality and fatty acid composition when grown in this region. This topic has not been addressed in the country; therefore, the objective of this research was to determine if plant density can affect those variables. The study was conducted in 2020 and 2021 in the zone of Osmaniye to determine total oil content of kernels, and contents of oleic acid, palmitic acid, arachidonic acid, linoleic acid, stearic acid, and lignoceric acid, as well as iodine value and oleic/linoleic ratio for the cultivars Halisbey, Rigel, Aysehanım, NC 7, and Masal. Plant response was in most instances different regardless of plant populations made up of a single row planting pattern with rows spaced 70 cm apart (95.000 plants ha-1) compared with a twin row planting pattern with rows spaced 20 cm apart on 90 cm centers with an intra-row distance of 15 cm (148.000 plants ha-1). It is concluded that no differences in oil quality and fatty acid composition were noted when comparing cultivars established at various combinations of planting pattern and plant population, but there were notable differences among the cultivars.